2020
DOI: 10.2116/analsci.20r006
|View full text |Cite
|
Sign up to set email alerts
|

Cell Analysis on Microfluidics Combined with Mass Spectrometry

Abstract: Cell analysis is of great significance for the exploration of human diseases and health. However, there are not many techniques for high-throughput cell analysis in the simulated cell microenvironment. The high designability of the microfluidic chip enables multiple kinds of cells to be co-cultured on the chip, with other functions such as sample preprocessing and cell manipulation. Mass spectrometer (MS) can detect a large number of biomolecules without labelling. Therefore, microfluidic chip coupled with MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 103 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…It is suggested that the Chip-MS device can be developed to be more portable, and the cell culture assembly for well culturing needs optimizing. Furthermore, chips with more advanced functions connected to MS, such as organ or single cell on chip, can provide a powerful mode for mimicking drug metabolism, cytotoxicity assessment, disease diagnosis, and gene analysis, which deserves more attention in future development [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the Chip-MS device can be developed to be more portable, and the cell culture assembly for well culturing needs optimizing. Furthermore, chips with more advanced functions connected to MS, such as organ or single cell on chip, can provide a powerful mode for mimicking drug metabolism, cytotoxicity assessment, disease diagnosis, and gene analysis, which deserves more attention in future development [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…cell seeding, incubation and automated analysis) is envisioned to develop as an effective clinical diagnostic point-ofcare device to meet the requirements of lower sample consumption, higher efficiency and detection sensitivity for clinical tests. Recently, chip-mass spectrometry (Chip-MS) has been used for clinical cell-based analysis, it can also facilitate the studies of microbial metabolism, treatment of diseases and drug screening to characterize the wide range of molecules from different metabolism activities [100,184]. Although lots of microfluidic devices have been developed, there are major hurdles in the microfluidic design for cell analysis in a more biomimetic microenvironment since the minor difference in microenvironments of cells can influence their phenotypes.…”
Section: Insight To Cell Physiology and Interactionsmentioning
confidence: 99%
“…The analysis of cellular metabolites plays a critical role in disease diagnosis [3][4][5] and drug development [6][7][8]. There have been ever-increasing research efforts in this field [9][10][11][12][13][14]. Among these metabolites, lactate is the main product of anaerobic metabolism.…”
Section: Introductionmentioning
confidence: 99%